Contribution of intraoperative radiotherapy (IORT) for therapeutic de‐escalation in early breast cancer: Report of a single institution's experience. Issue 5 (22nd January 2018) - Barrou, Julien; Tallet, Agnes; Cohen, Monique; Bannier, Marie; Buttarelli, Max; Gonzague, Laurence; Jauffret, Camille; Lambaudie, Eric; Rua, Sandrine; Tyran, Margueritte; Varela, Leonel; Houvenaeghel, Gilles
Abstract: The spread of systematic screening and the emergence of oncoplastic techniques allow more breast conservative treatment associating lumpectomy and external beam radiation therapy. In order to furthermore facilitate the patient's treatment, intraoperative radiation therapy (IORT) has been developed. The oncological safety of this technique has been studied, and is considered acceptable. Many questions remain unsolved in regard of the toxicity of this procedure as well as the patient's selection criteria. In this study, we present the first results and complications rate of patients treated by IORT in a single French institution. Between 2012 and 2015, all patients with breast cancer treated in a one‐step procedure associating lumpectomy and IORT were retrospectively included in a monocentric cohort. Acute and long‐term toxicities were evaluated using CTCAE v4.0 classification. 280 breast cancers were treated using IORT procedure. Additional external beam radiation therapy was requested for 45.7% patients. The acute complications rate was 14.6%, with 5 surgical revisions needed (1.78%). With a median follow up of 911 days, the long‐term grade‐3 toxicity rate was 1.1%. The only risk factor for local fibrosis was external beam radiation therapy (EBRT) (OR = 1.99; IC95 [1.05–3.81], P = 0.036). Three patients (1.07%) were diagnosed with local recurrence. The results from this cohort confirm the low complication and recurrence rate of IORT procedure. A good selection of patients is necessary in order to lower the EBRT rate and allow therapeutic de‐escalation. The classification of tumors into IHC subsets seems a good selection gate. Intraoperative radiation therapy appears to have a low toxicity rate with an acceptable local recurrence risk, and should therefore be considered as an option in the treatment of early breast cancer.